2015
DOI: 10.17222/mit.2014.087
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the tool geometry and process parameters on the static strength and hardness of friction-stir spot-welded aluminium-alloy sheets

Abstract: In this study, the effects of the tool geometry and welding parameters on the friction-stir spot-welding properties of AA 5754-H111 were studied. Two different tool-pin geometries were used and tensile shear tests were carried out to compare the weld strength. Hardness observations were also done. The optimum tool geometry for the mentioned material was determined as the circular pin tool and the tapered pin tool gave the lowest tensile shear load. Keywords: Al-alloys, friction-stir spot welding, mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The shoulder plunge depth and the tool rotational speed increased maximum failure load; however, the influence of the rotational speed is far less than the shoulder plunge depth. Guler et al [3] investigated how the tool geometry and the welding process parameters affect the static strength and hardness of FSSW AA 5754-H11 sheets. The pin profile, dwell time and the tool rotation rate were varied.…”
Section: Fssw Of Similar Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…The shoulder plunge depth and the tool rotational speed increased maximum failure load; however, the influence of the rotational speed is far less than the shoulder plunge depth. Guler et al [3] investigated how the tool geometry and the welding process parameters affect the static strength and hardness of FSSW AA 5754-H11 sheets. The pin profile, dwell time and the tool rotation rate were varied.…”
Section: Fssw Of Similar Alloysmentioning
confidence: 99%
“…Friction Stir Spot Welding (FSSW) as a linear modification of the FSW process has gained popularity to the extent of replacing the conventional Resistance Spot Welding (RSW) [1]. This practice produces a single spot welded joint from the overlapping adjacent material components [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Maximum and minimum hardness values were obtained as 92.2 and 71.6 HV at the tool The tensile shear load was increased for all the experiments, as the tool rotation speed was increased from 1350 to 1850 rpm. According to Güler [11] explained that an increase in the tensile shear load may be explained with the microstructural changes due to the heat generation at a stirring location. On the other hand, the tensile shear load was decreased when the tool rotational speed was increased from 1850 to 2530 rpm.…”
Section: Hardness Values Of Jointsmentioning
confidence: 99%
“…Among the proposed geometries, cylindrical pins were found to create the strongest welds at similar plunge depths than the others. Gu¨ler 20 compared the effects of circular pin tool and tapered pin tool on the static strength of the weld joint and reported that the circular pin had higher performance. The shoulder of the FSSW tool includes features to better contain material and improve the stirring process during welding.…”
Section: Tool Geometrymentioning
confidence: 99%